Bythaelurus bachi n. sp., a new deep-water catshark (Carcharhiniformes, Scyliorhinidae) from the southwestern Indian Ocean, with a review of Bythaelurus species and a key to their identification - Weigmann, Simon; Ebert, David A.; Clerkin, Paul J.; Stehmann, Matthias F.w.; Naylor, Gavin J.p. (Zootaxa, 2016)
A new deep-water catshark, Bythaelurus bachi, is described based on 44 specimens caught on the southern Madagascar Ridge in the southwestern Indian Ocean. The new species is the only stout-bodied Bythaelurus with oral papillae in the region and is distinguished from all congeners by the plain beige to light gray-brown coloration, high diversity in dermal denticle morphology, and presence of composite oral papillae. Despite resemblance in body shape, Bythaelurus bachi n. sp. is distinguished from its closest congener, B. naylori Ebert & Clerkin, 2015, by the presence of numerous large, partially composite papillae on the tongue and roof of the mouth (vs. papillae lacking), plain light coloration (vs. medium to dark brown ground color, light fin edges and a distinctly dark dusky-colored snout), only slightly enlarged dermal denticles on the anterior upper caudal-fin margin (vs. dermal denticles distinctly enlarged), a higher diversity in dermal denticle morphology in general, and smaller maximum size and size at maturity. The distinction of both species is also supported by molecular results. The new species differs from all other congeners in the western Indian Ocean in the stout body shape of large specimens, coloration, larger size, as well as several morphometrics, including larger claspers, longer eyes and dorsal fins, and shorter pelvic—anal and pelvic—caudal spaces. The genus is reviewed, a key to its species given.